Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR) tools. 4.1 Household Survey―Overview - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Ilboudo, Guy S.; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
Intra-household data helps to understand differences in disease identification and prevention, responsibilities, and decision-making for small ruminants between men and women